Local Charge Distribution in GaxPdy Intermetallics: Characterizing Catalyst Surfaces from Large-Scale Molecular Mechanics Simulations - Tanakorn Wonglakhon; Sven Maisel; Andreas Grling; Dirk Zahn (My University, 2024)
We combine the charge equilibration (QEq) method with the modified embedded atom model (MEAM) to describe a series of intermetallic GaxPdy compounds at near DFT accuracy. Apart from structure, energetics and elastic properties, a particular focus is dedicated to the partial charges on Ga and Pd sites in the bulk and on flat/terraced surfaces. By the example of GaPd2, we suggest a computationally very efficient approach to assessing the crystal faces and steps of interesting prospect for catalytic activity. To this end, we suggest enhanced catalytic activity of (010) faces by our simulation models that demonstrate particularly large charge transfer between surface Ga and Pd species, namely +0.8 and −0.4, whereas for the (100) and (001) faces local polarization is less than +0.6 and −0.3, respectively. Moreover, the study of rough surfaces is demonstrated from a small series of 10 nm sized simulation models featuring terraces. Local polarization of the atoms at the steps ranges from +0.5 to +1.1 and −0.5 to −0.3 for the Ga and Pd species, respectively.
Keywords: Intermetallics and Advanced Alloy Properties